Diagnostic and Demographic Differences Between Incarcerated and Nonincarcerated Youth (Ages 6-15) With ADHD in South Carolina. (May 2017) - Soltis, Samuel L.; Probst, Janice; Xirasagar, Sudha; Martin, Amy B.; Smith, Bradley H.
Objective: Analyze diagnostic and demographic factors to identify predictors of delinquency resulting in incarceration within a group of children/adolescents diagnosed with ADHD.Method: The study followed a cohort of 15, 472 Medicaid covered children/adolescents with ADHD, ages 6 to 15 inclusive, between January 1, 2003, and December 31, 2006. The Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev. [ DSM-IV-TR ]), 2000 Codes were used for qualifying diagnosis codes. Available demographic characteristics included race, sex, and residence. The outcome was incarceration at the South Carolina Department of Juvenile Justice during 2005-2006.Results: Among youth with ADHD, incarceration was more likely among black, male, and urban youth. Children/adolescents with comorbid ODD and/or CD were at greater risk compared with those with ADHD alone.Conclusion: Within ADHD-diagnosed youth, comorbid conditions and demographic characteristics increase the risk of incarceration. Intervention and treatment strategies that address behavior among youth with these characteristics are needed to reduce incarceration.